Non-replicative antibiotic resistance-free DNA vaccine encoding S and N proteins induces full protection in mice against SARS-CoV-2 - Alcolea, Pedro J.; Larraga, Jaime; Rodríguez-Martín, Daniel; Alonso, Ana; Loayza, Francisco J.; Rojas, José M.; Ruiz-García, Silvia; Louloudes-Lázaro, Andrés; Carlón, Ana B.; Sánchez-Cordón, Pedro J.; Nogales-Altozano, Pablo; Redondo, Natalia; et al. (Frontiers in Immunology, 2022)
SARS-CoV-2 vaccines currently in use have contributed to controlling the COVID-19 pandemic. Notwithstanding, the high mutation rate, fundamentally in the spike glycoprotein (S), is causing the emergence of new variants. Solely utilizing this antigen is a drawback that may reduce the efficacy of these vaccines. Herein we present a DNA vaccine candidate that contains the genes encoding the S and the nucleocapsid (N) proteins implemented into the non-replicative mammalian expression plasmid vector pPAL. This plasmid lacks antibiotic resistance genes and contains an alternative selectable marker for production. The S gene sequence was modified to avoid furin cleavage (Sfs). Potent humoral and cellular immune responses were observed in C57BL/6J mice vaccinated with pPAL-Sfs + pPAL-N following a prime/boost regime by the intramuscular route applying in vivo electroporation. The immunogen fully protected K18-hACE2 mice against a lethal dose (105 PFU) of SARS-CoV-2. Viral replication was completely controlled in the lungs, brain, and heart of vaccinated mice. Therefore, pPAL-Sfs + pPAL-N is a promising DNA vaccine candidate for protection from COVID-19.